Neotropical Polistinae (Vespidae) and the Progression Rule Principle: the Round-Trip Hypothesis - Carvalho, Antônio Freire; Menezes, Rodolpho Santos Telles; Somavilla, Alexandre; Costa, Marco Antônio F.; Lama, Marco Antônio Del (Neotropical Entomology, 2015)
The progression rule principle is based on the relation between centers of origin and basal forms, and the prediction that recently colonized areas are where novelties commonly occur. Using this concept as the null hypothesis, the aim of the present study was to test whether intuitive predictions of this model are confirmed in the Neotropical paper wasps, a group fairly studied through phylogenetic frameworks. The analyses consisted of a careful review of the distribution of different wasps of the subfamily Polistinae with available phylogenies and the association of this information with colonization routes. This procedure allowed the determination of a two-step colonization process in the Neotropical region based on the progression rule principle, for which the round-trip hypothesis is proposed. The first route (east to west) is seen in a small group of Polistes. This route is rare but strengthens the arising of paper wasps in the Americas in a Gondwanan scenario. The second route (west to east) is remarkably repeated in several other lineages. Thus, the northwestern Neotropics, mainly Amazon Forest, is proposed as the major center of origins for living Neotropical Polistinae and the round-trip hypothesis may explain both earlier and later colonization routes of the paper wasps analyzed. © 2015, Sociedade Entomológica do Brasil.
Keywords: Animals; Animals Dispersal; Classification; Evolution; Phylogeny; Wasp; Animals Distribution; Animal; Biological Evolution; Phylogeny; Wasps